البحث في إمكانية تحسين أداء الخلائط البيتومينية باستخدام نفايات أكياس النايلون - أحمد, رناء; كوسى, ميسم (Latakia University Journal -Engineering Sciences Series, 2019)
This research discussed the possibility of using waste plastic bags used as part of polymers to investigate their potential contribution to improving the properties of bituminous mixtures. The objectives of the study were to determine the effect of the addition of different percentages of the residues of the crushed nylon bags to the properties of the bituminous mixtures and to compare them with the characteristics of the traditional bituminous mixtures, Nylon bag waste was added in the form of grinded pieces ranging from (0.25-1) cm. The Marshall method for the design of bituminous mixtures was used to determine the optimum bitumen content as well as to test the properties of the bituminous mixture added to the nylon waste. Marshall's sample results showed that the optimum bitumen content was 5.5% of the bituminous mixture. The addition of five percent of bag waste was tested on the properties of bituminous mixtures (4-6-8-10-12)% Of the optimum bitumen content. The results indicated that nylon bag waste could be used as a propellant for the properties of bituminous mixtures as part of the sustainable management of plastic waste. The addition of bag waste by 8.67% of the bitumen weight gave greater stability to modified mixtures compared to conventional mixtures. In addition to lower density, air blanks and higher flow than the traditional mixture. ناقش هذا البحث إمكانية استخدام نفايات أكياس النايلون (البلاستيكية) المستعملة باعتبارها جزء من البولميرات للتحقق من احتمالات إسهامها في تحسين خصائص الخلائط البيتومينية. شملت أهداف الدراسة تحديد تأثير إضافة نسب مختلفة من نفايات أكياس النايلون المقطعة على خصائص الخلائط البيتومينية, ومقارنتها مع خصائص الخلائط البيتومينية التقليدية, إلى جانب تحديد النسبة المثلى لإضافة هذه النفايات, حيث تم إضافة نفايات أكياس النايلون على شكل قطع مطحونة تتراوح أبعادها بينcm (0.25-1), واستخدمت طريقة مارشال لتصميم الخلائط البيتومينية, وذلك لتحديد محتوى البيتومين الأمثل, وكذلك لاختبار خصائص الخليط البيتوميني المضاف إليه نفايات النايلون. أظهرت نتائج الإختبار أن محتوى البيتومين الأمثل هو 5.5% من وزن الخليط البيتوميني, وعند إضافة خمس نسب من نفايات الأكياس على خصائص الخلائط البيتومينية وهي (4-6-8-10-12)% من وزن محتوى البيتومين الأمثل, بينت نتائج الدراسات إلى أنه يمكن استخدام نفايات أكياس النايلون كمحسنات لخواص الخلائط البيتومينية كجزء من الإدارة المستدامة للنفايات البلاستيكية, وأن إضافة نفايات الأكياس بنسبة 8.67% من وزن البيتومين أعطى ثبات أكبر للخلائط المعدلة مقارنةً مع الخلائط التقليدية, بالإضافة لكثافة أقل ونسبة فراغات هوائية وانسياب أعلى من الخليط التقليدي.